THE DETERMINAN OF GOOD GOVERNANCE IMPLEMENTATION: A CASE IN MATARAM CITY INSPECTORATE - Ketut Hariyati; Baiq Anggun Hilendri Lestari; Nurabiah (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to predict the effect of the internal control system the government, the role of APIP and the performance of local government apparatus on the use of sound governance at the Mataram City inspectorate. This research is a type of associative research with a quantitative approach. The data used is primary information received by distributing questionnaires. The sampling technique used is a saturated sample by taking the entire population to be sampled, namely 47 employees of the Mataram City inspectorate. The data analysis tool used is Partial Least Square (PLS) version 3.0. The results of this study demonstrate that the implementation of good governance in the inspectorate of Mataram City is positively impacted by the functioning of the government internal control system, APIP, and local government apparatus. The theoretical significance of this study is that it strengthens the stewardship theory by illuminating the role that the Mataram City inspectorate plays in enhancing government internal control, streamlining internal control, and improving the efficiency of local government apparatus for results in good governance.